The path less traveled: the non-canonical NF-κB pathway in systemic lupus erythematosus - Montano, Hilary; Allen, Irving Coy; Reilly, Christopher M. (Frontiers in Immunology, 2025)
Systemic Lupus Erythematosus (SLE) is an autoimmune disease in which autoantibody production and cytokine dysregulation leads to systemic organ and tissue damage that can result in mortality. Although various environmental, hormonal, and genetic factors can contribute to disease pathogenesis, the cause of this disease is not known. Traditional treatment for this disease is centered around limiting inflammation using a variety of immunosuppresants including glucocorticosteroids as well as other therapeutics including anti-malarial drugs. More recently, selective immunosuppresives and biologics including Belimumab, a BAFF monoclonal antibody, and Anifrolumab, a monoclonal antibody that selectively binds to type 1 interferon receptor (INFAR1) blocking the biological activity of type 1 IFN, have been used with various success. It should be noted that BAFF is of particular relevance as signaling through BAFFR is a well characterized mechansim for non-canonical NF-κB signaling. While the canonical NF-κB pathway has been well studied and reported, the role of the non-canonical NF-κB pathway has been less investigated as to its role in autoimmunity. This pathway has been implicated in influencing pro-inflammatory immune responses while also regulating lymphocyte development. In this review, we aim to provide clarity on the relationship between the non-canonical NF-κB pathway and the role it plays in pathogenesis of SLE. The objective of this review is to summarize recent findings of the relationship of this pathway in autoimmunity and, more specifically, in lupus pathogenesis.